Kekerasan Berbasis Gender Online (OGBV) “Selebgram Membaca DM Cowok-Cowok Nakal | #SexEd” dalam Perspektif Semiotik Roland Barthes - Dewi Santika; Dewi sartika, Diana; Aidillah, Elita; Taqwa, M Ridhah; Istiqoma, Istiqoma; Randi, Randi (Universitas Negeri Surabaya, 2025)
The phenomenon of Online Gender-Based Violence (OGBV) has now become a global issue, along with the development of internet-based communication technology that provides easy access for many people. This condition often causes women to frequently become targets, resulting in losses in the form of physical, sexual, and psychological violence. These threats include acts of arbitrary deprivation of liberty in the public and private spheres. This study explores online gender-based violence and the impact of digital communication using Roland Barthes' semiotic model and qualitative visual ethnography. Key findings include: First, the video highlights direct messages received by the celebrity, including harassment and inappropriate content. Second, it reveals behaviours such as stereotypes, objectification of women, unwanted sexual advances, and the sharing of indecent images. Third, the underlying patriarchal culture reinforces the sexual objectification of women. This study aims to enhance understanding of online gender-based violence and contribute to semiotics and visual ethnography in this area.